CRIMINOLOGICAL VIEWS ON FAIRNESS AND JUSTICE (Law and world, 2015)
Scientific viewpoint, which is based on law and justice, constitutes a significant category of criminological thinking. The science of criminology should heavily influence the process of formation of these definitions. From a criminological point of view, law and justice by implication have the same meaning, while justice should serve as basis for law, since in the past it was used specifically under such meaning. The complexity of the matter also derives from the fact that in various disciplines of science – theology, jurisprudence, philosophy, sociology and psychology – numerous opinions exist with regard to these definitions. A standpoint recognized in criminology that every human by nature, without exception, is inclined to a commission of crime,does not prevent the provision stating that law should be based on justice from being true, due to the fact that it is an inseparable trait of a human to be a criminal. Thus, rules and principles of justice are established, followed by the establishment of law.